PRIMARY HEPATOCYTES AND MESENCHYMAL STEM CELL CULTURE EXPERIMENTS: A WAY TOWARDS BIOARTIFICIAL ORGANS - Azizi Miskon (Penerbit UTHM, 2014)
The Primary Hepatocytes and Mesenchymal Stem Cell Culture Experiments, A way towards Bioartificial Organs is written to foster further developments in cell-based therapies and bioartificial organs. This book details the principles and practical techniques which can be applied towards the productivity and functionality of cell cultures. It explains the effect of ECM proteins on beating duration of rat neonatal cardiomyocytes, the differentiation of P19CL6, the effects of induction technique, substrate and cell geometry, the effect of 3D culture system on cell functions and the cell preservation technique at room temperature. This book is intended for researcher, scientist, and postgraduate student in Tissue Engineering and Regenerative Medicine, and Biotechnology.